2018
DOI: 10.1242/dmm.035139
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of loss of NKX3.1 and inflammation in prostate cancer initiation

Abstract: Although it is known that inflammation plays a critical role in prostate tumorigenesis, the underlying processes are not well understood. Based on analysis of genetically engineered mouse models combined with correlative analysis of expression profiling data from human prostate tumors, we demonstrate a reciprocal relationship between inflammation and the status of the NKX3.1 homeobox gene associated with prostate cancer initiation. We find that cancer initiation in aged Nkx3.1 mutant mice correlates with enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Second, prostatitis is known to increase the risk of PCa [38] and alcohol enhances inflammation. Furthermore, chronic inflammation is known to create an immunosuppressive environment that negate antitumor immunity [39,40]. This provides an advantage for tumor formation and progression [41].…”
Section: Discussionmentioning
confidence: 99%
“…Second, prostatitis is known to increase the risk of PCa [38] and alcohol enhances inflammation. Furthermore, chronic inflammation is known to create an immunosuppressive environment that negate antitumor immunity [39,40]. This provides an advantage for tumor formation and progression [41].…”
Section: Discussionmentioning
confidence: 99%
“…Lineage plasticity, the ability of committed cells to change cell states through dedifferentiation or transdifferentiation, is an important mechanism for tissue repair ( Ge and Fuchs, 2018 ; Rajagopal and Stanger, 2016 ; Wahl and Spike, 2017 ). Cancer can co-opt this normal repair program to promote its initiation and progression ( Ge and Fuchs, 2018 ; Le Magnen et al, 2018 ). Un-like normal tissues, where lineage plasticity is a transient state during tissue repair, cancer cells exhibit persistent plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Schematic demonstration of changes in the expression profile of homeobox family genes in the control and ERN1 knockdown glioma cells under glucose deprivation; NS -no significant changes. with suppression of ERN1 knockdown glioma cells proliferation (Auf et al 2010) because this transcription factor functions as a tumor suppressor and can inhibits proliferation as well as invasion (Le Magnen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors play an important role in the malignant tumor growth, preferentially through ERN1 (endoplasmic reticulum to nucleus signaling 1) signaling pathway of endoplasmic reticulum stress (Minchenko et al 2015b, c;Tsymbal et al 2016a). The homeobox proteins represent an important group of transcription factors, which are related to tumorigenesis and has been largely investigated (Kataoka et al 2001;Guca et al 2018;Le Magnen et al 2018;Miyashita et al 2018;Chen et al 2019;Hamaidi et al 2019;Li et al 2019;Wang et al 2019). Recently, it was shown that transcriptional inhibitor ZEB2 (zinc finger E-box binding homeobox 2) functions as oncogene in human laryngeal squamous cell carcinoma (Li et al 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation